Der Anscheinsbeweis im schweizerischen Zivilprozess - Mettler, Christoph (sui generis Verlag, 2022)
This paper is devoted to a special form of "proving" in civil proceedings. The prima facie evidence is about proving a causal connection with life experience and common knowledge. The term "prima facie evidence" appears repeatedly in Swiss literature and case law, but what is meant by it often remains unclear. This paper addresses the open questions about prima facie evidence in Swiss civil procedure: It examines (1) what is meant by it, (2) what exactly is proved by it, (3) how the court forms its conviction, (4) how prima facie evidence is to be classified in the structure of burden of proof, standard of proof, and evaluation of evidence, and (5) what are the consequences for civil procedure.